Cold exposure induces the acquisition of brown adipocyte gene expression profiles in cattle inguinal fat normalized with a new set of reference genes for qRT-PCR. (October 2017) - Cao, K.X.; Hao, D.; Wang, J.; Peng, W.W.; Yan, Y.J.; Cao, H.X.; Sun, F.; Chen, H.
Abstract: The last few years have seen great advances in our understanding of browning in white adipose tissue (WAT) where white adipocytes take on characteristics of brown adipocytes. At present, the economic significance of browning for animal husbandry is beginning to be realized with the emerging evidence that browning affects body weight not only in human and rodent but in farm animals. Quantitative RT-PCR provides a quick and sensitive way to preliminary determine browning of WAT. However, there have been no established condition specific reference genes for browning of cattle WAT. As the results showed, the most two stable reference genes for diet treatment were Wdr33 ( M = 0.38) and Hdac3 ( M = 0.43), while the most three internal controls for temperature treatment were Hdac3 ( M = 0.28), Wdr33 ( M = 0.32), and Hprt1 ( M = 0.39) among the ten candidates. The mRNA relative expression levels of selective marker genes were normalized by normalization factor (geometric mean of control genes quantities). Cold exposure rather than high energy diet induced transcript elevations of brite specific markers ( Cited1, Tbx1 ), thermoregulatory markers (brown and beige versus white markers, i.e., Cidea, Cox7a1, Ucp1 ), mitochondrial biogenesis markers ( Nrf1, Nrf2, Tfam ), and transcription regulators (brown and beige versus white markers, i.e., Pgc1α ) ( P < 0.05) in cattle inguinal fat (iWAT). Quantitative RT-PCR is a preliminary study for WAT browning. In conclusion, cattle inguinal fat acquired brown adipocyte gene expression features upon cold acclimation with prerequisite identification of stable reference genes. Highlights: Two novel sets of reference genes were identified for diets and temperature treatments. Cattle inguinal fat acquired brite adipocyte gene expression features upon cold acclimation. Cattle backfat did not get brite adipocyte gene expression features upon cold or diet acclimation.